2014
DOI: 10.1111/jopy.12111
|View full text |Cite
|
Sign up to set email alerts
|

Renovating Situation Taxonomies: Exploring the Construction and Content of Fundamental Motive Situation Types

Abstract: The present work demonstrates a method for constructing theoretically based situational classifications and exploring their behavioral implications. Fundamental motives theory (FMT; Kenrick, Griskevicius, Neuberg, & Schaller, 2010; Kenrick, Neuberg, Griskevicius, Becker, & Schaller, 2010) proposes that humans have evolved seven specific social motives that would be differentially evoked by different situations. Experts in FMT used the Riverside Situational Q‐sort (RSQ) to describe prototypic motive‐relevant si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…To date, van Heck's () taxonomy remains the most inclusive and prominent among them, with 10 dimensions: conflict, joint working, intimacy/relationships, recreation, travelling, rituals, sport, excesses, serving and trading. More recently, Morse, Neel, et al (in press) classified situations in terms of seven motives identified as essential in evolutionary theory: self‐protection, disease avoidance, affiliation, kin care, mate seeking, mate retention, and status.…”
Section: Terminological Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, van Heck's () taxonomy remains the most inclusive and prominent among them, with 10 dimensions: conflict, joint working, intimacy/relationships, recreation, travelling, rituals, sport, excesses, serving and trading. More recently, Morse, Neel, et al (in press) classified situations in terms of seven motives identified as essential in evolutionary theory: self‐protection, disease avoidance, affiliation, kin care, mate seeking, mate retention, and status.…”
Section: Terminological Issuesmentioning
confidence: 99%
“…Thus, one can obtain classes from characteristics (e.g. by latent class analyses of DIAMONDS profiles; template matching: Morse, Neel, et al, in press), but going the other direction from classes to characteristics is problematic because characteristics can then only be inferred and not empirically derived. Finally, categorical approaches leave us wanting more.…”
Section: Considerations and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is little descriptive work on the forms of interdependence that are more frequently encountered in people's daily lives. Yet this type of empirical approach has been fruitfully applied in recent studies to identify, classify, and understand which situations are psychologically important in real-world settings (e.g., Brown, Neel, & Sherman, 2015;Morse, Neel, Todd, & Funder, 2015;Parrigon, Woo, Tay, & Wang, 2016;Rauthmann et al, 2014). can similarly be used to study the common types of interdependence that people experience daily.…”
Section: Interdependence In Daily Lifementioning
confidence: 99%
“…Various lines of empirical research have resulted in different taxonomies of situations according to their basic characteristics (e.g., Edwards & Templeton, 2005;Morse et al, 2015;Parrigon et al, 2016;Rauthmann et al, 2014;Yang, Read, & Miller, 2009). Recently, Gerpott and colleagues (2017) examined the relations between interdependence perceptions (i.e., SIS dimensions) and perceptions in terms of a newly developed situation taxonomy-the DIAMONDS-which includes eight dimensions of fundamental situation characteristics (Duty, Intellect, Adversity, Mating, pOsitivity, Negativity, Deception, and Sociality; Rauthmann et al, 2014).…”
Section: Perceptions Of Interdependence and Other Situation Taxonomiesmentioning
confidence: 99%